Concepts of health in long-term home care: An empirical-ethical exploration - Seidlein, Anna-Henrikje (Nursing ethics, 2020)
BackgroundConcepts of health have been widely discussed in the philosophy and ethics of medicine. Parallel to these theoretical debates, numerous empirical research projects have focused on subjective concepts of health and shown their significance for individuals and society at various levels. Only a few studies have so far investigated the concepts of health of non-professionals and professionals involved in long-term home care and discussed these empirical perspectives regarding moral responsibilities.ObjectivesTo identify the subjective concepts of the health of non-professionals (care recipients, informal caregivers) and professionals (registered nurses) involved in long-term home care and to discuss them against the background of existing normative guidelines addressing non-professionals and professionals’ responsibilities and rights concerning health.Research designA qualitative design was chosen to explore subjective concepts of health. Data were collected by semi-structured interviews; content analysis was applied according to Mayring.Participants and research contextTwenty-eight interviews were conducted with non-professionals and professionals in long-term home care arrangements in Northern Germany.Ethical considerationsEthics approval was obtained from the Institutional Review Board at the University Medicine Greifswald (BB123/16).FindingsNon-professionals and professionals consider health as a capability that enables them to participate in social activities and live their own lives according to their preferences. The former regard health particularly as a feeling and an attitude, the latter as the absence of disease with a focus on mental and emotional well-being. Both groups highlight the unsurpassable value of health and the personal responsibility for it.DiscussionNormative guidelines applicable to practice in long-term home care discuss responsibilities and rights unevenly and raise several problems regarding non-professionals and professionals’ subjective concepts of health.ConclusionIndividuals’ concepts of health are relevant for the subsequent interpretation of rights and responsibilities and should, thus, be reflected upon to address health-related needs effectively.